Why mass surveillance is an undesirable method for counter-terrorism (republicação) - Lopes, J. (Blog Changing World (Cei-Iscte), 2020)
This article aims to briefly explain why the deployment of these technologies is a flawed security measure for counter-terrorism. [The article was also previously published in the Blog Apostrophe Project]